Female healthcare undergraduates' scientific readiness for raising breast cancer awareness in Syrian conservative community - Mohammed Alshafie; Anas Bitar; Mhd Basheer Alameer; Dima Alhomsi; Massa Alfawal; Maher Saifo (BMC Medical Education)
Abstract Introduction Breast cancer is the most common and deadliest cancer in Syria, and early detection is crucial in managing it. This study aims to compare the knowledge levels of breast cancer risk factors, signs, and symptoms among female students in healthcare faculties (medicine, dentistry, and pharmacy) at Damascus University to identify existing disparities. The goal is to enhance breast cancer education and awareness across Syria by empowering healthcare students with insights. Methods An online self-administered questionnaire was shared on social media for female students of healthcare faculties to respond to. A total of 589 participants were included after applying the inclusion criteria. The questionnaire collected sociodemographic characteristics and evaluated the knowledge of breast cancer (BC) using breast cancer awareness measure (BCAM). The scale evaluates three sections: general knowledge, symptoms, and risk factors. Comparisons were conducted among the three faculties to gauge variations in knowledge levels. Results The majority of participants were aged between 21–23, the average of breast cancer knowledge among the whole sample was 24.7 ± 6.33 out of 40, with the internet and social media being the primary sources of information. Medical students had significantly higher knowledge scores compared to pharmacy and dentistry students. Higher faculty average grades were associated with higher knowledge scores, and there was a positive correlation between study years and breast cancer knowledge for medical and pharmacy students. There was no significant difference in breast cancer knowledge between participants with and without a medical relative or family history of breast cancer. Conclusion Breast cancer knowledge among female healthcare students in Damascus University is perfectible, which may not be enough to raise awareness. Awareness programs should be created to encourage leadership and accurate information dissemination, and professors should model good prevention practices.